INTERPRETASI EKOWISATA ABIOTIK AIR TERJUN SARAY BRUNYAU DI DESA RIAM PIYANG KABUPATEN KAPUAS HULU KALIMANTAN BARAT - Gunawan, Heri; Siahaan, Sarma; Yanti, Hikma (Universitas Tanjungpura, 2023)
Bunut Hulu District is one of the most important sub-districts in Kapuas Hulu Regency. Bunut Hulu has several very interesting attractions to visit, one of which is Saray Brunyau Waterfall located in Riam Piyang Village. Saray Brunyau Waterfall is included in the area with the status of a protected forest area. The purpose of this study is to obtain data on the potential of ecotourism objects and compile data on the interpretation of the ecotourism potential of the Saray Brunyau waterfall in Riam Piyang Village, Bunut Hulu District, Kapuas Hulu Regency. This research uses a descriptive survey method with direct observation techniques and direct interviews. Sampling of community respondents using purposive sampling. As a result of interviews and direct observations, 8 potentials can support the interpretation of ecotourism potential, namely Rice Fields, Fields, Rubber Plantations and Kratom Gardens, Tembawang Forest, Sebilit River, Saray Brunyau Waterfall, and Protected Forest. The results of the exploration are arranged into one tourist route, namely the abiotic interpretation path of ecotourism in Riam Piyang Village. The path from the settlement to the Saray Brunyau waterfall attraction is 3.50 km away.Keywords: Ecotourism, Interpretation, Kapuas Hulu Regency, Saray Brunyau, WaterfallAbstrakKecamatan Bunut Hulu merupakan salah satu kecamatan yang terletak di Kabupaten Kapuas Hulu. Bunut Hulu memiliki beberapa objek wisata yang sangat menarik untuk dikunjungi, salah satunya yaitu Air Terjun Saray Brunyau yang terletak di Desa Riam Piyang. Air Terjun Saray Brunyau masuk ke dalam kawasan yang berstatus kawasan hutan lindung. Tujuan dari penelitian ini yaitu mendapatkan data potensi objek ekowisata abiotik dan menyusun data interpretasi potensi ekowisata abiotik air terjun Saray Brunyau di Desa Riam Piyang Kecamatan Bunut Hulu Kabupaten Kapuas Hulu. Penelitian ini menggunakan metode survey yang bersifat deskriptif dengan teknik observasi langsung dan wawancara langsung. Pengambilan sampel responden masyarakat menggunakan purposive sampling. Hasil dari wawancara dan observasi langsung terdapat 8 potensi yang dapat mendukung interpretasi potensi ekowisata, yaitu Sawah, Ladang, Kebun Karet dan Kebun Kratom, Hutan Tembawang, Sungai Sebilit, Air Terjun Saray Brunyau, dan Hutan Lindung. Hasil eksplorasi tersebut disusun menjadi satu jalur wisata, yaitu jalur interpretasi abiotik ekowisata Desa Riam Piyang. Jalur dari pemukiman ke objek wisata air terjun Saray Brunyau hanya berjarak 3,50 km.Kata Kunci: Air Terjun, Ekowisata, Interpretasi, Kabupaten Kapuas Hulu, Saray Brunyau